Analisa Process Capability untuk Meningkatkan Kualitas Air Di Departemen Water Treatment Pada PT. Riau Prima Energi - Merry Siska; Eko Zaldianto (UIN Sultan Syarif Kasim Riau, 2012)
Improving the quality is something that is most essential for a company to exist in this competitive business world. The main products produced by PT. Riau Andalan Pulp and Paper, that is paper. The problem encountered is a paper that has splotches caused by high water turbidity values so that the product must be in rework. This requires a study to describe the process of water production in the Department of Water Treatment PT Riau Prima Energy as a business unit of PT. Riau Andalan Pulp and Paper. Method of process capability analysis using X and R control chart, which can be seen in the ability of the processes that occur after the water treatment process capability calculations. Based on the calculations, the value of Process Capability Index (Cp) of 1.19. This figure shows the process capability going well but need continuous monitoring in order to maintain the capability of the process. CPK values were in the range of 0.6031 1> CPK > 0, meaning that the average process within the limits of control, but there are some variations in the process falls outside the control limits. This indicates that the process a bit to meet customer specifications.Keywords : Quality, Process Capability, Kualitas, Kapabilitas Proses, X and R Control Chart, Specifications